My hero academia Vol. 9 - Horikoshi, Kōhei, 1986-; Cook, Caleb D. (San Francisco: VIZ Media LLC, 2014)
"What would the world be like if 80 percent of the population manifested superpowers called 'Quirks'? Heroes and villains would be battling it out everywhere! Being a hero would mean learning to use your power, but where would you go to study? The Hero Academy of course! But what would you do if you were one of the 20 percent who were born Quirkless? Middle school student Izuku Midoriya wants to be a hero more than anything, but he hasn't got an ounce of power in him. With no chance of ever getting into the prestigious U.A. High School for budding heroes, his life is looking more and more like a dead end. Then an encounter with All Might, the greatest hero of them all, gives him a chance to change his destiny ..."--
V. 1. Izuku Midoriya: origin -- v. 2. Rage, you damned nerd -- v. 3. All might -- v. 4. The boy born with everything -- v. 5. Shoto Todoroki : origin -- v. 6 Struggling -- v. 7. Kohei Horikoshi -- v. 10 All for one -- v. 11. End of the beginning, beginning of the end -- v. 12. The test -- v. 13. A talk about your quirk -- v. 14. Overhaul -- v. 15. Fighting fate -- v. 16. Red riot -- v. 17. Lemillion -- v. 18. Bright future -- v. 19. School festival Why he gets back up -- v. 20. School festival start!! -- v. 21. Why he gets back up -- v. 22. That which is inherited -- v. 23. Our brawl -- v. 24. All it takes is one bad day -- v. 25. Tomura Shigaraki: origin -- v. 26. The high, deep blue sky -- v. 27. One's justice -- v. 28. The thrill of destruction -- v. 29. Katsuki Bakugo rising
Pages numbered from right to left.
Description based on volume 1.
Rated T for teen.
Translated from the Japanese.
Keywords: Manga